Non-surgical management of ectopic pregnancy - Gupta, Vineeta; Nimonkar, Shweta; Chaudhari, Priyanka; Saxena, Namrata; Singh, Parul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Ectopic pregnancy is a condition when a fertilized ovum is implanted outside the uterine cavity. It is one of the important causes of maternal mortality and morbidity in India. Treatment includes expectant management, medical management and surgical management. Expectant and medical management are the treatment of choice for hemodynamically stable patients who do not want surgical treatment and are desirous of future fertility. The aim of study was to analyse the clinical profile, regimen of medical method used and outcome of non-surgical management in patients with ectopic pregnancy. Methods: It was a retrospective observational distributive study conducted at Shri Guru Ram Rai Institute of Medical and Health Sciences from January 2015 to December 2019. There were total 182 diagnosed cases of ectopic pregnancy during this duration. Out of them, 87 patients were given non-surgical management. Data was obtained from their medical records to analyse the clinical profile, outcome of expectant and medical management and efficacy of regimen used. Results: Total 87 patient out of 182 diagnosed cases of ectopic pregnancy were studied. Out of these, 57 (65.5%) patients were in the age group of 20 to 30 years, 44 (50.6%) patients were third gravidas and 32 (36.8%) patients did not have any live issue. Thirty three (37.93%) patients had haemoglobin less than 10 gm%, 41 (47.13%) patients had one or more previous caesarean sections and 73 (83.91%) patients had tubal ectopic pregnancy. Overall success rate with non-surgical management was 94.25%. Conclusions: Our study emphasised the role of expectant and medical management in stable patients of ectopic pregnancy and recommends to use methotrexate as therapy even when initial serum β HCG levels are more than 5000 IU and haemoglobin level less than 10 gm% under close monitoring.